Risk of colorectal cancer among immigrants to Ontario, Canada - Lawrence Paszat (BMC Gastroenterology, 2017)
Abstract Background The risk of colorectal cancer (CRC) varies around the world and between females and males. We aimed to compare the risk of CRC among immigrants to Ontario, Canada, to its general population. Methods We used an exposure-control matched design. We identified persons in the Immigration, Refugees and Citizenship Canada Permanent Resident Database with first eligibility for the Ontario Health Insurance Plan between July 1, 1991 and June 30, 2008 at age 40 years or older, and matched five controls by year of birth and sex on the immigrant’s first eligibility date. We identified CRC from the Ontario Cancer Registry between the index date and December 31, 2014. All analyses were stratified by sex. We calculated crude and relative rates of CRC. We estimated risk of CRC over time by the Kaplan-Meier method and compared immigrants to controls in age and sex stratified strata using log-rank tests. We modeled the hazard of CRC using Cox proportional hazards regression, accounting for within-cluster correlation by a robust sandwich variance estimation approach, and assessed an interaction with time since eligibility. Results Among females, 1877 cases of CRC were observed among 209,843 immigrants, and 16,517 cases among 1,049,215 controls; the crude relative rate among female immigrants was 0.623. Among males, 1956 cases of CRC were observed among 191,792 immigrants and 18,329 cases among 958,960 controls; the crude relative rate among male immigrants was 0.582.. Comparing immigrants to controls in all age and sex stratified strata, the log rank test p < 0.0001 except for females aged > = 75 years at index, where p = 0.01. The age-adjusted hazard ratio (HR) for CRC among female immigrants was 0.63 (95% CI 0.59, 0.67) during the first 10 years, and 0.66 (95% CI 0.59, 0.74) thereafter. Among male immigrants the age-adjusted HR = 0.55 (95% CI 0.52, 0.59) during the first 10 years and increased to 0.63 (95% CI 0.57, 0.71) thereafter. The adjusted HR > = 1 only among immigrants born in Europe and Central Asia. Conclusions The risk of CRC among immigrants to Ontario relative to controls varies by origin and over time since immigration.